Exploration of JAK/STAT pathway activation in ulcerative colitis reveals sex-dependent activation of JAK2/STAT3 in the inflammatory response - Calviño-Suárez, Cristina; Durán-Rubí, Mariña; Brea, José; Moreira, David; Ardao, Inés; Brocos-Mosquera, Iria; Ferreiro-Iglesias, Rocío; Porto-Silva, Sol; Nieto-Garcia, Laura; Varela, María José; Loza, María Isabel; Martínez, Antón L.; et al. (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is characterized by aberrant immune responses involving multiple inflammatory pathways, including JAK/STAT signaling. However, the specific roles and interactions of individual components within this pathway remain unclear.MethodsWe conducted a prospective, observational, single-center study enrolling 61 adult UC patients undergoing routine colonoscopy with endoscopic activity (Mayo Endoscopic Score > 0). Paired biopsies from inflamed and non-inflamed colonic mucosa were collected. Phosphorylation levels of JAK1, JAK2, JAK3, TYK2, STAT1, STAT3, and STAT4 were quantified by Western blot.ResultsInflamed tissue showed significantly increased phosphorylation of JAK2, JAK3, TYK2, STAT1, STAT3, and STAT4 compared to non-inflamed mucosa (p < 0.05), while JAK1 levels did not differ significantly. Correlation analysis revealed coordinated activation among JAK2, JAK3, TYK2, and STAT3, suggesting interdependent roles. Notably, male patients exhibited significantly higher activation of JAK2 and STAT3 than female patients (p < 0.05).DiscussionThese findings highlight a heterogeneous but important involvement of the JAK/STAT pathway in UC pathophysiology. The observed sex-specific differences and coordinated activation patterns suggest the value of personalized therapeutic approaches targeting specific components of this pathway.